2020
DOI: 10.1136/rmdopen-2020-001299
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of renal damage in systemic lupus erythematous patients: data from a multiethnic, multinational Latin American lupus cohort (GLADEL)

Abstract: AimA decrease in proteinuria has been considered protective from renal damage in lupus nephritis (LN), but a cut-off point has yet to be established. The aim of this study was to identify the predictors of renal damage in patients with LN and to determine the best cut-off point for a decrease in proteinuria.MethodsWe included patients with LN defined clinically or histologically. Possible predictors of renal damage at the time of LN diagnosis were examined: proteinuria, low complement, anti-double-stranded DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…Remission off-treatment and on-treatment and LDA-TC but not mLLDAS were associated with a lower probability of renal and ophthalmological damage. In the case of renal damage, this may be related to better control of disease activity, as it has been associated with renal damage in other cohorts27 28 and/or to the self-selection of a greater number of non-renal lupus in the remissions and LDA groups. Similar to our results, a longer percentage of the follow-up on remission on-treatment and LLDAS (including remission) were associated with a lower rate of some items of renal damage (end-stage renal disease and glomerular filtration rate <50%) in the Hopkins cohort 9.…”
Section: Discussionmentioning
confidence: 99%
“…Remission off-treatment and on-treatment and LDA-TC but not mLLDAS were associated with a lower probability of renal and ophthalmological damage. In the case of renal damage, this may be related to better control of disease activity, as it has been associated with renal damage in other cohorts27 28 and/or to the self-selection of a greater number of non-renal lupus in the remissions and LDA groups. Similar to our results, a longer percentage of the follow-up on remission on-treatment and LLDAS (including remission) were associated with a lower rate of some items of renal damage (end-stage renal disease and glomerular filtration rate <50%) in the Hopkins cohort 9.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary definitions are required for items such as pulmonary arterial hypertension, interstitial lung disease, renal impairment, osteoporotic fracture, cardiomyopathy, and stroke. For example, persistent proteinuria below the nephrotic range is predictive of a poor renal and overall prognosis (28)(29)(30)(31)(32). From a pediatric viewpoint, the SDI is missing items (e.g., growth restriction, delayed sexual maturation) (5).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, complement component 4 genes, near the major histocompatibility complex locus, reportedly generated a seven-fold variation in SLE risk [ 36 ]. Furthermore, studies have reported that anti-Sm antibodies [ 5 ] and low complement [ 37 ] are not only risk factors for LN but might also help to predict treatment response [ 38 , 39 ]. Based on previous research, we could reasonably assume that there is an association between serologic markers, such as anti-Sm antibodies and low complement, and LN.…”
Section: Discussionmentioning
confidence: 99%